2015
DOI: 10.1161/circresaha.115.307071
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Evolocumab on Vitamin E and Steroid Hormone Levels

Abstract: Rationale : Vitamin E transport and steroidogenesis are closely associated with low-density lipoproteins (LDLs) metabolism, and evolocumab can lower LDL cholesterol (LDL-C) to low levels. Objective: To determine the effects of evolocumab on vitamin E and steroid hormone levels. Methods and Results: After titration of backgroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(24 citation statements)
references
References 52 publications
(67 reference statements)
0
24
0
Order By: Relevance
“…Vitamin E and steroid-hormone levels were measured in 100 patients who participated in a substudy of a long-term evolocumab study 20. Relative to changes in cholesterol, there were no significant changes in serum vitamin E levels, LDL vitamin E levels, or red-cell membrane vitamin E levels.…”
Section: Safety Of Evolocumabmentioning
confidence: 99%
“…Vitamin E and steroid-hormone levels were measured in 100 patients who participated in a substudy of a long-term evolocumab study 20. Relative to changes in cholesterol, there were no significant changes in serum vitamin E levels, LDL vitamin E levels, or red-cell membrane vitamin E levels.…”
Section: Safety Of Evolocumabmentioning
confidence: 99%
“…Vitamin E levels instead decreased by a mean of 16% because of the involvement of lipoproteins in the transport of liposoluble vitamins; anyhow, when LDL-C concentrations were normalized, vitamin E raised to previous levels. 45 Moreover, from its discovery, we know that the human LDL-C receptor is saturated for plasma level >25 mg/dL; 46 this information further supports the safety of extreme LDL-C reduction in most patients.…”
Section: Tolerability and Safetymentioning
confidence: 84%
“…Alirocumab and evolocumab, either alone or in combination with statins and/or other lipid‐lowering therapies, have been shown in their respective phase 3 clinical trial programs (ODYSSEY and PROFICIO [Program to Reduce LDL‐C and Cardiovascular Outcomes Following Inhibition of PCSK9 In Different Populations]) to significantly reduce LDL‐C levels by up to 60% from baseline (depending on dosing regimen; Table) in patients with hypercholesterolemia, including those with familial hypercholesterolemia, moderate to very high cardiovascular risk, and statin intolerance 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62. The inclusion/exclusion criteria and other details of each phase 3 ODYSSEY and PROFICIO trial are shown in Table S2.…”
Section: Pcsk9 Inhibitors and Their Effects In Patients With Diabetesmentioning
confidence: 99%